2021
DOI: 10.1098/rspb.2021.1129
|View full text |Cite
|
Sign up to set email alerts
|

Kinship dynamics: patterns and consequences of changes in local relatedness

Abstract: Mounting evidence suggests that patterns of local relatedness can change over time in predictable ways, a process termed kinship dynamics. Kinship dynamics may occur at the level of the population or social group, where the mean relatedness across all members of the population or group changes over time, or at the level of the individual, where an individual's relatedness to its local group changes with age. Kinship dynamics are likely to have fundamental consequences for the evolution of social behaviour and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 80 publications
1
51
0
Order By: Relevance
“…Social effort given is likely to be similar in magnitude but more widely distributed for dispersers. [155,156,158] age Figure 1. Challenges to disentangling explanations for age-related changes in adult social behaviour.…”
Section: §2c(ii) Kinship Dynamicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Social effort given is likely to be similar in magnitude but more widely distributed for dispersers. [155,156,158] age Figure 1. Challenges to disentangling explanations for age-related changes in adult social behaviour.…”
Section: §2c(ii) Kinship Dynamicsmentioning
confidence: 99%
“…In this way, within-individual declines in sociality with age might occur as a result of population-level demographic changes. Local demography can also affect how average relatedness to potential social partners changes with age, which might result in advantageous within-individual shifts in social behaviour because individuals may gain indirect fitness by supporting relatives [ 155 ]. Theoretical models have demonstrated that changing patterns of relatedness can favour different patterns of helping and harming behaviour with age [ 156 ], which, in some specific contexts, is suggested to play an important role in selecting for late-life helping behaviour, such as the cessation of females' reproduction in favour of promoting their offspring's reproductive success [ 42 , 157 ].…”
Section: Explanations For Social Ageing In Mammalian Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…behaviour is generally starting to realize that the social environment is very likely different for individuals differing in their age;Croft et al 2021 discuss this with respect to kinship (see alsoRodrigues 2018). Our work shows that the social state, i.e.…”
mentioning
confidence: 66%